2010
DOI: 10.1159/000236903
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Disease and Outcome among Patients with Acute Diverticulitis

Abstract: Background: This study was designed to evaluate the natural history of patients admitted for acute diverticulitis. Methods: Nine hundred and seventy-seven patients admitted to Oulu University Hospital for acute symptoms of diverticular disease during the 20-year period from 1986 to 2005 were identified using a database. Results: Six hundred and ninety-five patients were admitted for uncomplicated diverticulitis and 282 for complicated diverticulitis. The patients admitted for uncomplicated diverticulitis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
(29 reference statements)
0
11
0
20
Order By: Relevance
“…Similarly, in a prospective study involving 232 patients with acute diverticulitis, Shaikh et al found that the incidence of subsequent surgery for the 191 surviving patients who were discharged without resection was statistically greater for patients under 50 years of age compared with those over 50 years of age (38% vs 15%; P = 0.015) [14]. This greater incidence of a complicated outcome in younger patients after successful medical treatment of acute diverticulitis has been challenged by four retrospective studies that did not find any difference in the outcome between younger and older patients [23][24][25][26]. However, all of these studies were underpowered.…”
Section: The Predictive Value Of Ct (Level Of Evidence 2b Grade Of Rmentioning
confidence: 99%
“…Similarly, in a prospective study involving 232 patients with acute diverticulitis, Shaikh et al found that the incidence of subsequent surgery for the 191 surviving patients who were discharged without resection was statistically greater for patients under 50 years of age compared with those over 50 years of age (38% vs 15%; P = 0.015) [14]. This greater incidence of a complicated outcome in younger patients after successful medical treatment of acute diverticulitis has been challenged by four retrospective studies that did not find any difference in the outcome between younger and older patients [23][24][25][26]. However, all of these studies were underpowered.…”
Section: The Predictive Value Of Ct (Level Of Evidence 2b Grade Of Rmentioning
confidence: 99%
“…Recently, Makela et al published a review of 977 patients admitted for acute diverticulitis during a 20-year period [57]. The authors found that even with 2 or more previous admissions for acute diverticulitis, sigmoid resection remained unjustifiably excessive.…”
Section: Introductionmentioning
confidence: 99%
“…Estudios de la historia natural de la diverticulitis no complicada (99) Después del adecuado tratamiento médico de un episodio de diverticulitis aguda, cerca de un tercio de los pacientes desarrollarán un segundo episodio y un tercio de estos pacientes tendrán un tercer episodio, por lo que la recomendación debe basarse en la edad del paciente, la comorbilidad asociada, la frecuencia y gravedad de los episodios de diverticulitis y la persistencia de la sintomatología después de la resolución del episodio agudo. La mayoría de los pacientes que tienen una diverticulitis complicada, la presentan en su primer episodio, por lo que una política de resección de colon programada posterior a la resolución del primer episodio de diverticulitis aguda no complicada, no parece que reduciría la probabilidad de requerir una cirugía de urgencia (3,22,29,30,99,101,103,104,105) .…”
Section: Opción Terapéutica Dosisunclassified
“…La Sociedad de Cirugía del Colon y el Recto, en su guía más actual del tratamiento de la enfermedad diverticular, recomienda realizar la cirugía programada basándose en las características individuales de cada paciente (99) y varios estudios como el de Jyrky y cols. ratifican esta práctica (103) . Además indican que el número de episodios de diverticulitis no complicada, no es necesariamente una indicación quirúrgica (3,12,22,29,30,92,99,100,101,103,104,105) .…”
Section: Referenciaunclassified
See 1 more Smart Citation